(untitled) (Applied Biological Research, 2022)
This study was designed to encapsulate curcumin in chitosan nanoparticles synthesized by ionic gelation method. In dissolution studies, curcumin was found insoluble in water, slightly soluble in HCl, H2SO4 and phosphate buffer saline (PBS) [pH 6.8, 8.4] but highly soluble in ethanol and dimethyl sulfoxide. Fourier transform infrared spectroscopy (FTIR) analysis of pure curcumin revealed the presence of different functional groups. In an attempt to optimize the best suited nanoparticles, three different formulations were prepared with increasing concentration of curcumin. Curcumin (CRN) @ 500 mg kg-1 was found to be the best formulation with particle size of 844 nm, zeta potential of -32.7 mV, encapsulation efficiency of 70.9%, and loading efficiency of 9.2%. Further, it was characterized by FTIR, X-ray diffraction spectroscopy (XRD), and scanning electron microscopy (SEM) analysis. In vitro drug release studies showed the initial burst release followed by slow and steady release up to 100 h. Finally, pure CRN anticancer activity is compared with chitosan nanoparticles (CNPs) loaded with CRN. Percentage of cells viable decreased with increase in the concentration of both CRN and CRN-CNPs-1. CRN loaded in CNPs was founmore effective than pure CRN. Thus, the study revealed the successful encapsulation of curcumin and increasing therapeutic in in the treatment of breast cancers.